Imunoexpressão linfócitos (T CD4+ / T CD8+) e protéinas do check point imune (PD-1 E PD-L1) em lesões periapicais primárias e persistentes - Macêdo Filho, Robeci Alves (2023)
Introduction: Persistent periapical lesions (PL2) are associated with persistent painful symptoms and progression of bone resorption processes, even after endodontic retreatment. It is believed that there is a difference in the microenvironment between persistent and primary periapical lesions. Mechanisms of evasion of the immune response may occur in infectious processes. Among the main ones is the union of the complex programmed cell death receptor (PD-1) and its PDL-1 ligand, which can also bind to T lymphocyte–associated antigen 4 (CTLA-4) leading to a decrease in the proliferative capacity of lymphocytes as well as a lower production of cytokines by activated T cells, thus contributing to the creation of an immunosuppressive microenvironment in persistent periapical lesions. Objective: To evaluate the subpopulations of CD4+ and CD8+ T lymphocytes and the immunoexpression of proteins related to the check point (PD1 and PD-L1) in persistent and primary periapical lesions, aiming to provide more information about the immunological mechanisms involved in the pathogenesis of these lesions. Methodology: Cross-sectional, observational study, 0 PD-1 and PD-L1 in 05 random fields of the epithelial lining (intraepithelial lymphocytes) and 05 fields of the connective tissue of the CRs capsule. In periapical granulomas, 05 random fields of greater immunoexpression of these antibodies were evaluated. Counts of T CD4+ and T CD8+ lymphocytes and immunopositive cells for PD-1 and PD-L1 were performed in each field, which were summed and the average number of immunopositive cells was estimated. Nonparametric Mann-Whitney and Spearman correlation tests were used for data analysis, considering a significance level of 5% (p<0.05). Results: grade III of inflammatory infiltrate predominated in all lesions CR1 (7/10 – 70%), CR2 (6/10 – 60%), GP1 (10/10 – 100%) and GP2 (7/9 – 77 .8%). In CR2, 50% of the cases had atrophic epithelia and 50% hyperplastic epithelia. In CR1, hyperplastic epithelium predominated (70%). There were higher percentages of T CD8+ and T CD4+ lymphocytes in LP2, but the difference was not statistically significant. LP2 lesions showed higher percentages of CD8 immunoexpression when compared to LP1, with a statistically significant difference (p=0.014), mainly in CR2. There was a statistically significant difference in PD-1 immunoexpression in GP2 when compared to CR2 (p= 0.004). PD-L1 showed a significant difference in immunoexpression in the cystic capsule between CR2 and CR1 (p=0.000), as well as, in relation to clinical behavior, with greater immunoexpression in CR2 (cytoplasm p=0.000 and nucleus p=0.003). In PL2 there was a positive correlation of cytoplasmic PD-L1 immunoexpression with T CD8+ expression in GP2 (r= 0.881 and p= 0.004) and correlation of PD-L1 immunoexpression in epithelium with T CD4+ expression in CR2 (r= 0.886 and p = 0.001). Conclusion: LP2 reveal variations in their cellular constituents and clinical behaviors. The results suggest a potential cytotoxic microenvironment, with greater amounts of T CD8+ and a positive regulation of PD-1/PD-L1 immunoexpression, which has as its basic function the induction of regulatory lymphocytes for the process of apoptosis or anergy, thus decreasing the response host defense against these persistent infections.